EFFECTS OF TERRORISM ON SPORTS ACTIVITIES IN KHYBER PAKHTUNKHWA: A CASE STUDY OF DISTRICT SWAT AND BUNER - Ajbar Khan; Dr. Yasmeen Iqbal; Shahzaman Khan (The Sky, 2017)
The study investigates terrorism and its effects on sports activities. To find out ways and means to promote sports activities in the affected areas, to determine the trend of common people and athletes in the conflicted areas of Khyber Pakhtunkhwa towards sports activities and to evaluate the Governments’ efforts in reducing the consequences of terrorism on Sports activities. The study is limited to the male athletes of Government High and Higher Secondary Schools of District Swat and Buner in Khyber Pakhtunkhwa Province of Pakistan. The study consists of 200 male students, 100 each from District Swat and Buner. Respondent are students of secondary schools (9th, 10th class) and higher secondary schools (11th, 12th), with age range of 13-22 years. Simple random method was used for sampling purpose. The effects of terrorism on sports activities were assessed through interview and self-administered questionnaire. SPSS (Statistical Package for Social Science) version 15 was used to analyze the data. Descriptive statistics like measurement of central tendency and measurement of dispersion were utilized to describe the data. Work has been done on 200 respondents. According to the result, 78% mothers of the respondents were illiterate while 22% were educated, whereas 46% fathers were illiterate while 54% were educated. 98% families became IDPs and 90% schools were closed down due to terrorism. 86% respondent attitude was positive toward sport activities and 88% schools were found to have playgrounds. 86% parents allow their children to participate in sports and 72% take part in sports activities after school time. 74% respondents were optimistic for a positive change in near future. 10% received threats who want to participate in sports activities. 26% respondent felt outside danger. 34% schools have been used by law enforcement agencies. Finally it was observed that majority of the people have positive attitude towards sports activities despite the fact that majority of schools had been closed for a long period due to terrorism.